2013
DOI: 10.1017/s1368980013002978
|View full text |Cite
|
Sign up to set email alerts
|

The phenomenon of micronutrient deficiency among children in China: a systematic review of the literature

Abstract: Objective: The present study aimed to review the literature on micronutrient deficiency and other factors influencing a deficiency status among children living in China. Design: A systematic review was performed to analyse the literature. Setting: Studies were identified through a search of PubMed and secondary references. Subjects: Children living in China aged less than 18 years. Results: Sixty-one articles were included. The prevalence of vitamin A deficiency decreased to approximately 10 % in 1995-2009. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 56 publications
0
37
0
Order By: Relevance
“…When foods that are poor sources of nutrients become major sources in the diet, it is quite reasonable to speculate that risk of nutrient shortfall could exist. A recent review reported that anaemia prevalence of children under 5 years old in China was 11.3 % in 2005 [19] and the peak of anaemia prevalence was between infants aged 6 to 12 months [20]. In this study, growing-up milk remained to be one of the major contributors to energy and many nutrients among toddlers, which indicated that growing-up milk was commonly consumed among toddlers of the study.…”
Section: Majority Of Energy and Nutrients Come From Few Foodsmentioning
confidence: 55%
“…When foods that are poor sources of nutrients become major sources in the diet, it is quite reasonable to speculate that risk of nutrient shortfall could exist. A recent review reported that anaemia prevalence of children under 5 years old in China was 11.3 % in 2005 [19] and the peak of anaemia prevalence was between infants aged 6 to 12 months [20]. In this study, growing-up milk remained to be one of the major contributors to energy and many nutrients among toddlers, which indicated that growing-up milk was commonly consumed among toddlers of the study.…”
Section: Majority Of Energy and Nutrients Come From Few Foodsmentioning
confidence: 55%
“…For example, previous large-scale studies of infants and young children have estimated ID prevalence rates of 5%–20% in Europe and 9% in the US (1921). The estimated IDA prevalence rates are 3%–9% in Europe and 2.1% in the US, whereas Chinese and Brazilian studies have reported far higher prevalence rates of anemia (28.2% and 36.0%, respectively) (19213031). Few large-scale Korean studies have evaluated the prevalence of ID among healthy term infants, and one small-scale Korean study from 2007 reported a similar prevalence of ID among exclusively breastfed term infants from a large suburb, compared to the present study (32).…”
Section: Discussionmentioning
confidence: 99%
“…According to Warthn-Medina et al (2015) micronutrients needs in the first two years of child's life is very high to meet physiological requirements (Warthon-Medina et al, 2015). Micronutrients deficiency contribute to impairment of child growth, cognitive and motor development and affect immunological functioning (Rohner et al 2013;Wieser et al, 2013;Wong et al, 2014). Thus, infants should receive the most nutrient-rich foods to meet their optimal nutrient needs per each age group.…”
Section: Discussionmentioning
confidence: 99%